Modeling and parameter identification of composite power supply for plug-in HEV. Issue 2 (February 2021) - Sun, Jingxia
Abstract: By analyzing the characteristics of the components of PHEV composite power supply, the voltage characteristics, temperature characteristics and capacity efficiency of batteries and supercapacitor are clarified. The dynamic voltage characteristics of batteries and supercapacitor are simulated by modeling the composite power supply. Based on the cross current discharge characteristics of lithium-ion batteries and the application conditions of batteries in PHEV, the second-order linear battery model recommended in PNGV is selected in this paper; for supercapacitor, the simplified RC branch model can be used to describe the characteristics, and the experimental data are used to identify the parameters involved in the model, and the accuracy of the model is verified.